An exploratory study on intrinsic and extrinsic motivational values for participating in knowledge sharing activities - Mansor, Zuraina; Mohd Salleh, Lailawati; Mustapha, Mazlina (Medwell Journals, 2016)
The flow of knowledge in an organization can be depending on the attitude and behaviour of the individual. Knowledge sharing is a social interaction culture, involving the exchange of employee knowledge, experiences and skills through the whole department or organization (Lin). The types of organizations also give impact to the sources of motivation. In public institutions, workers realized that their organizations have a standard system, a flat hierarchy structure even the salary and promotion opportunities cannot compete with business organizations. This study aims to explore the knowledge-sharing to identify the intrinsic motivational elements for KS activity in a public higher education institution using the qualitative approach.